Profiles of Risk and Protection for Violence and Bullying Perpetration Among Adolescent Boys. (1st January 2020) - Taliaferro, Lindsay A.; Doty, Jennifer L.; Gower, Amy L.; Querna, Katherine; Rovito, Michael J.
ABSTRACT: BACKGROUND: Violence and bullying perpetration among boys are major public health problems. We address gaps in the literature by examining: (1) how risk and protective factors co‐occur, and (2) how different risk/protection profiles are associated with violence and bullying perpetration among adolescent boys. METHODS: Data came from the population‐based 2016 Minnesota Student Survey. The analytic sample included boys in grades 8, 9, and 11 (N = 63, 818). Latent profile analyses identified patterns of 22 behavioral, intrapersonal, family, and school and community risk/protective factors. Logistic regression analyses examined how these patterns related to violence and bullying perpetration. RESULTS: We identified 5 groups: Class 1: Low risk, high safety, high connectedness ; Class 2: Low risk, moderate safety, moderate connectedness ; Class 3: Moderate risk, high safety, moderate connectedness ; Class 4: High risk, moderate safety, low connectedness ; and Class 5: High risk, low safety, low connectedness . Compared to Class 1, Class 5 students had the highest odds of all for violence and bullying perpetration. Class 4 students also demonstrated high odds of violence and bullying, compared to Class 1. Though not as high as Classes 4 or 5, Class 2 and 3 students showed higher odds for both outcomes, compared to Class 1. CONCLUSIONS: Substantive variations exist in boys who engage in violence and bullying. We highlight cumulative, co‐occurring risk factors, connectedness to parents and other prosocial adults (eg, teachers), and school and neighborhood safety as important factors to address in school health programs seeking to prevent violence and bullying perpetration among boys.